2017
DOI: 10.1002/2017jc012882
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biological characteristics of the winter‐summer transition in the Central Red Sea

Abstract: The Central Red Sea (CRS) lies between two distinct hydrographic and atmospheric regimes. In the southern Red Sea, seasonal monsoon reversal regulates the exchange of water between the Red Sea and the Indian Ocean. In the northern Red Sea, intermediate and occasionally deep water are formed during winter to sustain the basin's overturning circulation. Highly variable mesoscale eddies and the northward flowing eastern boundary current (EBC) determine the physical and biogeochemical characteristics of the CRS. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 29 publications
5
29
0
Order By: Relevance
“…Given the interaction of the two eddies, entrainment of cooler, saltier offshore water by the onshore flow between the two eddies may mix with the coastal Gulf of Aden water to increase its salinity (∼39.4) and reduce its temperature (∼26°C). Zarokanellos et al () pointed out that eddies may block or redirect the flow of the EBC. In this example, the EBC appears to be entrained by the southern anticyclonic eddy, and is constrained to the coast and mixed with offshore water by the interaction of the eddy pair.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the interaction of the two eddies, entrainment of cooler, saltier offshore water by the onshore flow between the two eddies may mix with the coastal Gulf of Aden water to increase its salinity (∼39.4) and reduce its temperature (∼26°C). Zarokanellos et al () pointed out that eddies may block or redirect the flow of the EBC. In this example, the EBC appears to be entrained by the southern anticyclonic eddy, and is constrained to the coast and mixed with offshore water by the interaction of the eddy pair.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that eddy‐induced upwelling events, with variable position and lifespan, interact with the vertical and horizontal thermohaline circulation by injecting deep‐water nutrients into the surface layers (Gaube et al, ; Kürten et al, ; Martin & Richards, ). Elsewhere, it is shown that the interaction of the EBC with mesoscale eddies and may function as a barrier to this northbound thermohaline flow of the EBC, by deflecting the EBC toward the west and offshore (Figure , Zarokanellos et al, ). Models, remote‐sensing of ocean color and altimetry indicate that the CRS is dominated by recurrent and occasionally dipole eddies (Chen et al, ; Raitsos et al, ; Zhan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Model simulations (e.g., Eshel & Naik, 1997;Sofianos & Johns, 2003;Yao, Hoteit, Pratt, Bower, Zhai, et al, 2014) and some observations (Bower & Farrar, 2015;Zarokanellos, Papadopoulos, et al, 2017) indicate that the surface EBC carries warm and relatively low-salinity surface waters, becoming cooler, more saline, and denser as it progresses northward due to intense air-sea fluxes. The composites suggest that the high evaporation associated with the large-scale westward winds may induce surface water mass transformation in the surface EBC.…”
Section: Effects Of Dry-air Outbreaks On the Red Sea Evaporationmentioning
confidence: 98%
“…Despite these differences, they have a very similar pattern. During winter, this region is dominated by the northward-flowing surface Eastern Boundary Current (EBC) that is believed to be an essential piece of the Red Sea overturning circulation (Bower & Farrar, 2015;Sofianos & Johns, 2003;Zarokanellos, Papadopoulos, et al, 2017). The WHOI/KAUST mooring is located on the southern flank of this high evaporation pool (Figure 12).…”
Section: Effects Of Dry-air Outbreaks On the Red Sea Evaporationmentioning
confidence: 99%
“…These have been captured in various independent observations, including remotely sensed sea surface height (SSH) data (Bower & Farrar, 2015;Raitsos et al, 2017;Zhan et al, 2014), sea surface temperature (SST) data (Papadopoulos et al, 2015), chlorophyll-a data (Raitsos et al, 2013), synthetic aperture radar imagery (Karimova & Gade, 2014), and in situ observations (Sofianos & Johns, 2007;Zarokanellos et al, 2017;Zhai & Bower, 2013). These have been captured in various independent observations, including remotely sensed sea surface height (SSH) data (Bower & Farrar, 2015;Raitsos et al, 2017;Zhan et al, 2014), sea surface temperature (SST) data (Papadopoulos et al, 2015), chlorophyll-a data (Raitsos et al, 2013), synthetic aperture radar imagery (Karimova & Gade, 2014), and in situ observations (Sofianos & Johns, 2007;Zarokanellos et al, 2017;Zhai & Bower, 2013).…”
Section: Introductionmentioning
confidence: 99%